Structural integrity assessment of a partially filled tank pertainning to liquid sloshing - Muhamad Abid Hasan, Hasan (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Liquid cargo contained in a partially filled tank is known to experience sloshing movement when subjected to maneuvering disturbances. Large amplitude of liquid slosh can be induced within a partially filled road tank vehicle under mild to severe maneuvers, which may severely affect the structural integrity of the tank. The study aims to develop a three dimensional finite element model for transient liquid slosh inside a tank, predict the effects of liquid slosh on the structural integrity of the tank, investigate the effectiveness of baffles designs and performance in suppressing the liquid slosh, and improve the design of the tank to assure the safety of such a liquid cargo. A comprehensive experimental study is conducted within a scaled down model of a partially filled cylindrical tank without baffles to analyze the liquid slosh movement under longitudinal deceleration excitations. A three dimensional finite element analysis model of transient liquid slosh is developed for the partially filled cylindrical tank with and without baffles by using Arbitrary Lagrangian Eulerian (ALE) formulation in LSDYNA program. The results of the experimental and simulation models of the transient liquid slosh are compared to validate the three dimensional ALE model of the liquid slosh, which demonstrates a fairly good agreement as far as the bulk fluid behavior is concerned inside the partially filled cylindrical tank. Additionally, a comparison of the strain results showed the trends of the simulation results are similar to the experimental results. Further, the transient liquid slosh analyses are carried out to investigate the performance of baffles incorporated inside the tank, and evaluate the effectiveness of the configurations of anti slosh baffles in limiting the transient liquid slosh. The presence of baffles significantly suppresses the liquid slosh within the partially filled cylindrical tank, and thus improves the structural integrity of the tank. The analysis also determines the most effective baffle design in suppressing the transient liquid slosh within the partially filled cylindrical tank, which therefore minimizes the load shift of the liquid slosh. In conclusion, the comparison between the experimental and simulation results provided good agreements that validated the capability of the ALE formulation to describe the transient liquid slosh behavior inside the tank, the transient liquid slosh generates forces applied on the tank wall, the behavior of the liquid slosh depends on the baffles configurations which significantly influence the movements of liquid slosh, the presence of baffles inside the tank works as dampers which effectively suppress the liquid slosh, and finally the results suggest that the baffle type of semi circular orifice at the upper half section BT6 is the most effective type which provides good performance in suppressing the transient liquid slosh inside the tank.